Promotion of Student Self-Regulation from Transformational Evaluation Processes: Case Applied to the Innovation Program in University Teaching - Jiménez Mena, Karen Nicole.; Álvarez Cisternas, Marisol del Carmen. (Grupo de Pesquisa em Gestão Social e Ambiental, 2024)
Objetive: To describe from a transformational model based on student empowerment, the implementation of active and collaborative evaluation procedures among students, with the purpose of promoting self-regulation of their learning. Theoretical Framework: The new conception of evaluation has involved the incorporation of new evaluative agents in the process, focused on an evaluation for learning and how learning, integrating students as active participants in their own learning and evaluation, developing self-regulation and metacognitive, promoting student empowerment, and the delegation of evaluative responsibilities from a dialogic and collaborative model. Method: The methodology adopted for this research arises from a qualitative approach and includes an intrinsic case study, for which the ALE–Q Questionnaire - Evaluation Climate as learning and empowerment in Higher Education by Ibarra-Sáiz, María Soledad, was applied. & Rodríguez-Gómez, Gregorio. Results and Discussion: It can be confirmed that greater student participation in learning evaluation processes promotes student autonomy and responsibility, which mobilizes more inclusive, empowered and democratic evaluation processes. The possibility that students can make value judgments and commit to their own learning, which mobilizes learning throughout life.v Implications of the research: The research involved delving into the learning evaluation procedures in higher education and promoting from here a change from the traditional evaluation paradigm towards a transformational evaluative approach based on student empowerment, this paradigmatic break highlights what is legitimized found among higher education teachers to implement traditional, unilateral evaluation models with little student participation. Originality/Value: The study stresses traditional learning evaluation models versus transformational evaluative models, where the active, collaborative and empowered participation of students is promoted, producing a break in the linearity of how the evaluation processes have been conceived.
Promoción de la autorregulación estudiantil desde procesos de evaluación transformacionales: caso aplicado a programa de innovación en docencia universitaria
Promoção da autoregulação dos alunos a partir de processos de avaliação transformacionais: caso aplicado ao programa de inovação no ensino universitário
Keywords: Autorregulación; Innovaciones educativas; Aprendizaje; Empoderamiento